Genomic characterization of polyextremotolerant black yeasts isolated from food and food production environments - Cai, Shiyu; Snyder, Abigail B. (Frontiers in Fungal Biology, 2022)
Black yeasts have been isolated from acidic, low water activity, and thermally processed foods as well as from surfaces in food manufacturing plants. The genomic basis for their relative tolerance to food-relevant environmental stresses has not been well defined. In this study, we performed whole genome sequencing (WGS) on seven black yeast strains including Aureobasidium (n=5) and Exophiala (n=2) which were isolated from food or food production environments. These strains were previously characterized for their tolerance to heat, hyperosmotic pressure, high pressure processing, hypochlorite sanitizers, and ultraviolet light. Based on the WGS data, three of the strains previously identified as A. pullulans were reassigned as A. melanogenum. Both haploid and diploid A. melanogenum strains were identified in this collection. Single-locus phylogenies based on beta tubulin, RNA polymerase II, or translation elongation factor protein sequences were compared to the phylogeny produced through SNP analysis, revealing that duplication of the fungal genome in diploid strains complicates the use of single-locus phylogenetics. There was not a strong association between phylogeny and either environmental source or stress tolerance phenotype, nor were trends in the copy numbers of stress-related genes associated with extremotolerance within this collection. While there were obvious differences between the genera, the heterogenous distribution of stress tolerance phenotypes and genotypes suggests that food-relevant black yeasts may be ubiquitous rather than specialists associated with particular ecological niches. However, further evaluation of additional strains and the potential impact of gene sequence modification is necessary to confirm these findings.